2009
DOI: 10.1080/01421590903134160
|View full text |Cite
|
Sign up to set email alerts
|

Virtual patients in a virtual world: Training paramedic students for practice

Abstract: Collaborative learning through case-based or problem-based learning (PBL) scenarios is an excellent way for students to acquire knowledge and develop decision-making skills. However, the process is threatened by the movement towards more self-directed learning and the migration of students from campus-based to workplace-based learning. Paper-based PBL cases can only proceed in a single direction which can prevent learners from exploring the impact of their decisions. The PREVIEW project, outlined in this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 6 publications
1
76
0
Order By: Relevance
“…The use of VR for medical and critical care training has been established for over a decade (Hsu et al, 2013) as a means to simulate hazardous environments and provide students with problem based learning scenarios. VR in medical education ranges from dedicated simulation programs through to virtual environments in Second Life (Conradi et al, 2009). A comparative study by Cone, Serra, and Kurland (2011) indicated the efficacy of VR as a platform for paramedic student education.…”
Section: Introductionmentioning
confidence: 99%
“…The use of VR for medical and critical care training has been established for over a decade (Hsu et al, 2013) as a means to simulate hazardous environments and provide students with problem based learning scenarios. VR in medical education ranges from dedicated simulation programs through to virtual environments in Second Life (Conradi et al, 2009). A comparative study by Cone, Serra, and Kurland (2011) indicated the efficacy of VR as a platform for paramedic student education.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Virtual patients have been defined as computer programs that simulate lifelike clinical scenarios in which the learner becomes the health care professional making therapeutic decisions. 21 Virtual patients allow educators to assess student decisionmaking skills regarding course content in a safe, highfidelity environment, while allowing students to learn and err in private.…”
Section: Introductionmentioning
confidence: 99%
“…This is because when using problem-based learning in virtual learning environments the discussion forums result in a linearity in learning which is unhelpful for team work. Using problem-based learning in SL student experience suggests both in this study and other related PREVIEW studies [3][4][5][6][7] , that students value in-world interactive collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Further related papers were published elsewhere. [3][4][5][6][7] It is argued here that the current lack of pedagogical underpinning has introduced a number of difficulties, little understanding about which kinds of pedagogies best work in virtual worlds and which do not and what the impact is of using these 3D spaces on student learning and student engagement. It is suggested here that these difficulties might be overcome by using approaches that readily combine pedagogy with technology, thereby shifting from the VLEs to IVWs.…”
Section: Introductionmentioning
confidence: 99%